The community-based PhD : complexities and triumphs of conducting CBPR - McCleary, Alexandra; Atalay, Sonya, 1968- (Book collections on Project MUSE., 2022)
"This volume explores the complex and nuanced experience of doing community-based research as a graduate student. Written by graduate students for graduate students, authors from a range of scholarly disciplines share their experiences with CBPR in the arts, humanities, social sciences, public health, and STEM"--